2019
DOI: 10.1002/slct.201901621
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Dimethyl Carbonate via Transesterification of Propylene Carbonate with Methanol Catalyzed by Bifunctional Li‐Al Nano‐composite

Abstract: A series of binary mixed metal oxides (MMOs) were synthesized by combination of Mn+/Al3+ (Mn+= Li, Mg, Co, Ni, Zn) via co‐precipitation method and screened for transesterification of propylene carbonate (PC) with methanol. The aim of this study was to understand the role of acid‐base properties of MMOs on the activity and selectivity towards dimethyl carbonate (DMC) synthesis. The MMOs were characterized in detail by XRD, BET, TEM, NH3 and CO2‐TPD techniques. Catalysts synthesized by various combination of Mn+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The intensity of NH 3 adsorption at 298 • C on the NaOH_T + R catalyst was 1.5 times higher than with the NaHCO 3 _T + R catalyst. Moreover, an asymmetric adsorption peak at about 430 • C on the NaOH_T + R catalyst may present the acid sites of NiO [69]. However, the NaHCO 3 _T + R catalyst does not find any adsorption peak at 430 • C. It implies that more NiAl 2 O 4 , rather than reduced NiO, formed on the surface of the NaOH_T + R catalyst.…”
Section: Mechanism Of Carbon (Coke) Formation In Ethanol Steam Reform...mentioning
confidence: 93%
See 1 more Smart Citation
“…The intensity of NH 3 adsorption at 298 • C on the NaOH_T + R catalyst was 1.5 times higher than with the NaHCO 3 _T + R catalyst. Moreover, an asymmetric adsorption peak at about 430 • C on the NaOH_T + R catalyst may present the acid sites of NiO [69]. However, the NaHCO 3 _T + R catalyst does not find any adsorption peak at 430 • C. It implies that more NiAl 2 O 4 , rather than reduced NiO, formed on the surface of the NaOH_T + R catalyst.…”
Section: Mechanism Of Carbon (Coke) Formation In Ethanol Steam Reform...mentioning
confidence: 93%
“…The resulting value of the ratio of acid/base sites was 0.519. A previous study [69] described that the base strength distribution of the M-Al mixed oxide relies on the M n+ metal cation (such as Li + ) used for incorporation with Al 3+ cation (Li + /Al 3+ ). In our study, the Li + promoter in the Al 2 O 3 structure could effectively provide the Li + -O 2− acid-base pairs.…”
Section: Mechanism Of Carbon (Coke) Formation In Ethanol Steam Reform...mentioning
confidence: 99%
“…This route has various added advantages as it does not corrode the equipment and does not produce waste. 12 Several catalysts are used that can help in overcoming the activation energy of the reaction, thus enabling this reaction to occur in the favor of the product. The heterogeneous catalysts such as bimetallic catalysts gave better results in terms of yield as well as selectivity due to the active basic and acidic sites available for the adsorption of reactants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it becomes important to adopt the other route, transesterification, which gives higher yield and selectivity in comparison to the direct synthesis route. This route has various added advantages as it does not corrode the equipment and does not produce waste …”
Section: Introductionmentioning
confidence: 99%
“…LDH is widely used in ion adsorption, , medical treatment, flame retardants, and catalysis , due to its special structure and properties. As a catalyst, LDH can effectively facilitate the esterification and transesterification of small molecules. Additionally, LDH is often used as a reinforcing nanomaterial to enhance the mechanical properties of epoxy resin. , Recent work has demonstrated that the anion species and metal ions of LDH have a significant impact on the curing of epoxy resin. For example, Karami et al found that ZnAl-NO 3 -LDH could promote the ring-opening curing reaction of epoxy resin due to the catalytic effect of Zn 2+ and NO 3 – . , However, most reports only focus on the effect of LDH on the curing behavior of the epoxy-amine system, and thus the effect of LDH on the epoxy-carboxylic acid system remains to be explored. Therefore, the LDH is expected to catalyze the curing of an epoxy vitrimer based on DTER and to simultaneously enhance the repairable efficiency and mechanical properties, instead of only the mechanical reinforcement effect of other nanomaterials such as graphene oxide and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%